ANALISIS PENGARUH KELEMBAGAAN TERHADAP KEBERHASILAN HTI-TRANSMIGRASI : Studi kasus di daerah Riau - Setiasih Irawanti; B D Nasendi; Retno Maryani; Suwidji Basuki (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Transmigration-based Timber Estate (TTE) is an effort to combine transmigration programme and Timber Estate development, and it involves many institutions which sometimes have conflicting interests. The objective of this study is to identify existing institution, efficiency and effectiveness of TTE programme and to study the socio-economic condition of transmigrant.The result of analysis shows that community around forest adhered to traditional institution. And their understanding on the prevailing external institution of government and timber estate concession were relatively low. The aspiration of local community for having plantation usually ended up in chopping activity. Average chopped area was 13 Ha per household. This practice supported by village officials and made this institutional problem more complicated. Their claim of forest area as a customary right was triggered by their insecurity of a continous access to forest as a source of their livelihood.Only about 21,5% local community were willing to be relocated as a local transmigrant and only about 25-30% of those were worked effectively for timber estate, so TTE programme is yet considered effective in relocating, modifying way of life and improving participation of local community. The proprietary right on agricultural land in TTE programme was only 0,25Ha, so giving proprietary right on agricultural land in adequate extent is highly recommended.There were three kind of activities in timber estate development, namely land preparation,nursery, planting and weeding. Wage payment system on land preparation activity was contractual wages at about Rp 85.000-115.000 per Ha. The wage of nursery, planting and weeding activities were about Rp 4. 250- 4. 750 per day. Compared to the Regional Minimum Wages (UMR) for this region in 1993 which was Rp 4.150, labor wage of timber estate development met its social function. Average income labor family per month in land preparation was Rp 253. 600, whereas for planting and weeding was Rp 173. 100 and which nursery activity was Rp 163. 100. Compared to the Minimum Physical Needs (KFM) for this region which was Rp 266.197 in 1993, the earning of labor family from TTE was lower. It means their living condition had not improved yet.